From Pluripotency to Early Differentiation of Human Embryonic Stem Cell Cultures Evaluated by Electron Microscopy and Immunohistochemistry - Jacobsen, Janus Valentin; Andersen, Claus Yding; Hyttel, Poul; Møllgård, Kjeld (IntechOpen, 2011)
None